Are masks effective as source control in index influenza patients? a Systematic review. (November 2021) - Burdick, Halie N.; Maibach, Howard
Highlights: Current recommendations call for influenza patients to wear masks in clinical visits. Many studies have been conducted with multiple interventions making it hard to delineate the true efficacy of masks. This review found there were few studies and weak supporting evidence for mask recommendations. Abstract: Background: The use of facemasks for infection prevention has become widely accepted. Current recommendations include influenza patients wearing a mask in a medical setting. Here we systematically reviewed randomized control trials on mask efficacy in index influenza patients to prevent transmission. Methods: PubMed, Google Scholar, and Web of Science were searched and articles were included if they fit the criteria of 1) randomized control trial, 2) influenza, 3) mask efficacy, 4) influenza patients with masks for source control, 5) in vivo, and 6) article was in English. Results: The results point to no difference in influenza transmission between medical mask and control groups. However, there have been several attempts at explaining this finding. Conclusion: This review found there were few studies and weak supporting evidence for mask recommendations. We hope for larger, randomized control trials in the hospital setting that evaluate the efficacy of masks as a means of source control in influenza infected patients.